2023
DOI: 10.1186/s12889-023-15342-2
|View full text |Cite
|
Sign up to set email alerts
|

Promoting HPV vaccination at school: a mixed methods study exploring knowledge, beliefs and attitudes of French school staff

Abstract: Background HPV vaccine coverage in France remained lower than in most other high-income countries. Within the diagnostic phase of the national PrevHPV program, we carried out a mixed methods study among school staff to assess their knowledge, beliefs and attitudes regarding HPV, HPV vaccine and vaccination in general, and regarding schools’ role in promoting HPV vaccination. Methods Middle school nurses, teachers and support staff from four French … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 27 publications
(50 reference statements)
0
22
0
2
Order By: Relevance
“…However, a study showed half of the school staff and parent respondents in a study in French doubted the safety of HPV vaccination. Therefore, it is advised to enhance school staff knowledge about the evidence-based practice of HPV before giving information to adolescents in school [ 57 ]. Most of all, it is important to make school staff aware about their potential influence on adolescents’ and parents’ attitudes toward HPV vaccination [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a study showed half of the school staff and parent respondents in a study in French doubted the safety of HPV vaccination. Therefore, it is advised to enhance school staff knowledge about the evidence-based practice of HPV before giving information to adolescents in school [ 57 ]. Most of all, it is important to make school staff aware about their potential influence on adolescents’ and parents’ attitudes toward HPV vaccination [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows the characteristics of the included studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Studies were conducted in various geographic settings: five studies from Asia (Hong Kong, Japan, the Republic of Korea, and Uzbekistan), two studies from North and South America (Canada and Peru), five studies from Africa (Kenya, Nigeria, and Tanzania), and three studies from Europe (France and Scotland).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Five studies [23,28,29,33,36] had unclear reporting of whether the relationship between the researcher and participants had been adequately considered during the interviews. All three mixed-methods studies [27,32,34] were compliant with the quality criteria except for the item regarding adequate rationale for using a mixed-methods design to address the research question (only one study [27] met this criterion). Overall, the included studies were relevant to the topic, presented their data and research findings coherently, and reflected on their methodological limitations.…”
Section: Quality Assessment Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…20 First, published evidence on facilitators and barriers to the uptake of HPV vaccination, and on existing interventions to improve vaccination in general and for HPV in particular among adolescents helped identify the framework of a 3-component intervention: (1) educating and motivating adolescents in middle schools; (2) training general practitioners (GPs) on up-to-date HPV information and motivational interviewing techniques; and (3) free HPV vaccination at school. A diagnostic phase was then carried out to identify-among others-knowledge, beliefs, barriers, and preferences around HPV vaccination and the sociodemographic factors associated with each, [21][22][23][24] to define the exact content of each component to appropriately address vaccine hesitancy in our population. The final version of the PrevHPV multicomponent intervention was constructed with the target populations to fit to all French adolescents, regardless of their sociodemographic characteristics.…”
Section: Introductionmentioning
confidence: 99%